FORMULASI JAGUNG MANIS (Zea mays L. saccharata) DAN UBI JALAR ORANYE (Ipomoea batatas L.) TERHADAP SIFAT FISIKOKIMIA DAN SENSORI SUSU NABATI - meidini, ema; raharjo, dwi; lestari, oke (Fakultas Pertanian Universitas Tanjungpura, 2019)
The goal of this research was to find out of the best formulation of sweet corn and sweet potato on physicochemical characterized and sensory properties in vegetable milk. This research used randomized block design (RBD) of one factor, namely the proportion of sweet corn (g) and sweet potato(g), consist of 6 levels are (100 : 0, 90 : 10, 80 : 20, 70 : 30, 60 : 40, 50 : 50) with 5 replications. The data obtained were analyzed using ANOVA 5%, with further testing using BNJ test with a level of 5%. The best treatment using the Effectiveness Indexs Test. The results showed that 50 g sweet corn : 50 g sweet potato is the best formulation basev on physicochemical and sensory characterized. The physicochemical of vegetable milk were protein content (0,31 %), viscosity (3,37 cP), Vitamin C (22,66 mg/100g), Total Soluble Solid (11,53 °Brix), and pH (6,80). The best sensory characteristics were the flavor of (3,50), the color of (3,67), aroma of (3,20), and preference 0f (3,47). Keywords : sweet corn, sweet potato, vegetable milk